Jogo digital e analogias: uma proposta para o ensino de Cinética Química - Almeida, Gustavo Martins Alves de [UNESP] (2015)
The difficulties in approach of concepts related to physical chemistry as well as young people's interest for new media were the main factors that motivated this dissertation. We conducted a study on the use of analogies and its facilitator role in the process of teaching and learning chemistry concepts. Thus, a game was designed, which works as an analogy involving theoretical concepts about motion of particles and about the kinetic model of gases. The construction of the game was made using Game Editor, a software designed specifically for this purpose, and was based on game design concepts, in order to become an interesting and attractive media. The game development path was also one object of analysis in this work